Sprint training in hypoxia promotes aerobic capacity and phosphofructokinase activity - Puype, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Contradictory findings are reported regarding whether exercise training in hypoxia may further stimulate training-induced adaptations compared with similar training in normoxia. Although there are different possibilities to profit from the hypoxic stimulus, the strategy of "live low-train high" or so called "intermittent hypoxic training" is receiving major attention (Vogt et al., 2001). In this study we compared the effects of 6 weeks sprint interval training (SIT) in normoxia or in hypoxia on exercise performance. Muscle glycolytic and oxidative capacity were analysed as well. Methods: Healthy male volunteers (19-36yrs) performed SIT (3d/week, 4-9 x 30-s sprints) under either hypoxic (3000m; FiO2 14.5% O2; HYP, n=10) or normoxic (0m; FiO2 ~ 20.9% O2; NOR, n=9) conditions. The control group did not train (CON, n=10). Before and after the training period the subjects performed a maximal incremental exercise test followed by a 10` time trial in normoxia and hypoxia, in addition a needle biopsy was taken from the m.vastus lateralis Results: Compared with CON, maximal power output was enhanced in HYP (+5-7%, P<0.05), but not in NOR, as measured at sea level as well as at moderate altitude. Moreover, HYP increased the workload corresponding with the onset of blood lactate accumulation in normoxia compared with NOR (P<0.05) and CON (P<0.01). Nevertheless, HYP and NOR produced similar improvements (~5%) in both 10-min time trial performance and mean power output in a 30-s sprint. Interestingly, muscle phosphofructokinase activity was stimulated by 60% in HYP and was higher than NOR following SIT (P<0.05). The activity of citrate synthase was not differently affected by NOR and HYP. Discussion: Our data demonstrates that intermittent sprint training in hypoxia is an effective strategy to increase whole-body oxidative capacity at sea level and at altitude as well as to enhance glycolytic enzyme activity in skeletal muscle. The increase in PFK activity may be caused by a HIF-1á dependent mechanism because HIF-1á triggers PFK transcription (Wenger, 2002). Vogt M., Hoppeler H. (2010). Progress in cardiovascular diseases 52: